Deposition of Pd nanoparticles on the walls of cathodically hydrogenated TiO2 nanotube arrays via galvanic displacement: A novel route to produce exceptionally active and durable composite electrocatalysts for cost-effective hydrogen evolution. (May 2018) - Lačnjevac, Uroš; Vasilić, Rastko; Tokarski, Tomasz; Cios, Grzegorz; Żabiński, Piotr; Elezović, Nevenka; Krstajić, Nedeljko
Abstract: Noble metal-based materials are inevitable components of cathodes for the hydrogen evolution reaction (HER) in future water electrolysis systems for clean hydrogen fuel production. However, designing active and durable nanostructured catalysts with low amount of costly noble metals is still a great challenge. Herein, we show that Pd nanoparticles (NPs) can be synthesized on the highly developed surface of anodically grown TiO2 nanotube (TNT) arrays by applying a simple galvanic displacement strategy. In a two-step procedure, air-annealed TNT arrays are first cathodically protonated and then partially reoxidized by Pd(II) ions from a PdCl2 solution while providing a scaffold for the metallic Pd deposit. Structural and electrochemical characterizations reveal that the Pd content and the width of the Pd-populated zone of the tube walls are in correlation with the tube length. The Pd@TNT composites display remarkable HER activity in 1 M HClO4 delivering a current density of −10 mA cm −2 at an overpotential of −38 mV and a Tafel slope of only −13 mV/dec. More impressively, the mass and apparent activity of the Pd@TNTs is superior to even commercial Pt/C at higher current densities. The composites also show stable chronopotentiometric response over 25 h and a negligible HER overpotential increase after potential cycling tests. The exceptional performance of the Pd@TNT cathodes is assigned to the unique semiconducting properties of the three-dimensional, interactive TNT supporting structures that, on the one hand, provide abundance of Pd active sites with optimized atomic hydrogen binding energy for the cathodic HER, but on the other hand, prevent anodic degradation of the Pd catalyst. Graphical abstract: fx1 Highlights: Nanosized Pd spontaneously deposits on cathodically protonated TiO2 nanotube arrays. Pd loading depends on galvanic displacement duration and average tube length. Prepared Pd@TNTs surpass Pt/C in apparent and mass activity towards HER in 1 M HClO4 . Pd@TNTs show excellent stability under long-term and accelerated degradation tests. Superior HER performance is attributed to interactive 3D TiO2 semiconducting support.